Oral Rehabilitation of Oral Cancer Patients Using Zygomatic Implant-Supported Maxillary Prostheses with Magnetic Attachment: Three Case Reports - Hisashi Ozaki; Hiromasa Sakurai; Yukie Yoshida; Hideyuki Yamanouchi; Mitsuyoshi Iino (Case Reports in Dentistry)
Maxillectomy for malignant tumor often results in a maxillary defect and serious oral dysfunction. A prosthesis is usually provided for postoperative oral rehabilitation of such patients with maxillary defects. However, the further the resected region extends, the less stable the prosthesis becomes, due to insufficient bone and tooth support. Therefore, in many cases, conventional resection dentures may not be adequate to restore the oral function. Effective utilization of dental and zygomatic implants may help to restore oral function in patients with severe maxillary defects. This clinical report describes the management of three patients with severe maxillary defects following cancer ablative surgery who were rehabilitated using maxillary prostheses with magnetic attachments supported by dental and zygomatic implants. Occlusal reconstruction was performed with removable prostheses supported with two or four implants and magnetic attachment. The oral function was evaluated before and after prosthodontic treatment with implants using the Oral Health Impact Profile (OHIP-14) and functional chewing score. Results indicated improvement in all cases. These findings show that quality of life (QOL) and oral function were improved.